Strategi Preservasi dan Konservasi Bahan Pustaka di Dinas Perpustakaan Kota Padangsidimpuan - Waldan Warid Sitompul; Laila Rohani; Abdi Mubarak Syam (Lembaga Pengembangan Kinerja Dosen, 2024)
Padangsidimpuan City Library Service, preservation and conservation of existing library materials has not been carried out as it should. This can be seen when repairing damaged library materials in the processing room. Repairing damaged library materials can be repaired properly, this can be done if the librarian who repairs the library materials understands and understands the repair of damaged library materials so that they are maintained and can be preserved, but the reality is that there are professional staff/librarians who repair, maintain and preserve the materials. library does not have a library education background. Apart from that, to conserve library materials, a room for maintaining and preserving library materials is also needed, not only the processing room but also other rooms. To maintain and preserve library materials, pay attention to the storage or location of the library materials. The type of research used by the author is descriptive research with a qualitative approach. Qualitative methods are research methods that are intended to understand the phenomena experienced by research subjects holistically by describing them in the format of linguistic words, in a specific context experienced and utilized by various scientific methods. This research resulted that the Padang Sidempuan City Library Service has a preservation strategy or several methods used by officers in preserving library materials, namely binding, patching and connecting paper, glue or adhesive, lamination, nails/bolts for books and cleaning the library room. In conservation activities for library materials at the Padang Sidempuan city Library Service, the library team has implemented several strategies that have been carried out in the management of library materials at the Padang Sidempuan city Library Service, including preserving library materials, maintaining library materials, repairing damage to library materials, carry out assistive tools in library material conservation activities, and use methods in using library material conservation activities. Regarding factors causing damage, damage to library materials can be caused by several factors, including internal and external. The Padang Sidempuan City Library Service itself relates to the causes of damage to library materials which originate from biological factors, physical factors, chemical factors, or other factors such as human error.